Antifibrotic Effects of Amyloid-Beta and Its Loss in Cirrhotic Liver - Gayane Hrachia Buniatian; Ralf Weiskirchen; Thomas S. Weiss; Ute Schwinghammer; Martin Fritz; Torgom Seferyan; Barbara Proksch; Michael Glaser; Ali Lourhmati; Marine Buadze; Erawan Borkham-Kamphorst; Frank Gaunitz; et al. (Cells, 2020)
The function and regulation of amyloid-beta (Aβ) in healthy and diseased liver remains unexplored. Because Aβ reduces the integrity of the blood-brain barrier we have examined its potential role in regulating the sinusoidal permeability of normal and cirrhotic liver. Aβ and key proteins that generate (beta-secretase 1 and presenilin-1) and degrade it (neprilysin and myelin basic protein) were decreased in human cirrhotic liver. In culture, activated hepatic stellate cells (HSC) internalized Aβ more efficiently than astrocytes and HSC degraded Aβ leading to suppressed expression of α-smooth muscle actin (α-SMA), collagen 1 and transforming growth factor β (TGFβ). Aβ also upregulated sinusoidal permeability marker endothelial NO synthase (eNOS) and decreased TGFβ in cultured human liver sinusoidal endothelial cells (hLSEC). Liver Aβ levels also correlate with the expression of eNOS in transgenic Alzheimer’s disease mice and in human and rodent cirrhosis/fibrosis. These findings suggest a previously unexplored role of Aβ in the maintenance of liver sinusoidal permeability and in protection against cirrhosis/fibrosis via attenuation of HSC activation.